Neuronal substrates underlying stress resilience and susceptibility in rats. - Fabia Febbraro; Katrine Svenningsen; Thao Phuong Tran; Ove Wiborg (PLoS ONE)
Background Stress and stressful life events have repeatedly been shown as causally related to depression. The Chronic Mild Stress rat model is a valid model of stress-induced depression. Like humans, rats display great heterogeneity in their response to stress and adversity. Hence some individuals are stress-sensitive and prone to develop depression-like behaviour in response to modest stressors, while others are stress-resilient and remain essentially symptom free. Objectives Compared to the large body of research, which describes stress-induced maladaptive neurobiological changes, relatively little attention has been devoted to understand resiliency to stress. The aim of the present study was to identify changes in neuronal activity, associated with stress-resilient and stress-susceptible chronic mild stress endophenotypes, by examining c-Fos expression in 13 different brain areas. Changes in c-Fos expression have been reported as associated to stressful conditions. Methods Stress-induced modulation of neuronal activation patterns in response to the chronic mild stress paradigm was mapped using the immediate early gene expression c-Fos as a marker. Quantification of the c-Fos-like immunoreactivity responses was done by semi-automated profile counting procedures and design-based stereology. Results Exposure to chronic mild stress significantly altered c-Fos expression in a total of 6 out of 13 investigated areas. Chronic mild stress was found to suppress the c-Fos response within the magnocellular ventral lateral geniculate nucleus of both stress subgroups. In the the lateral and ventral orbital cortices of stress-resilient rats, the c-Fos like immunoreactivity response was also repressed by stress exposure. On the contrary the c-Fos response within the amygdala, medial habenula, and infralimbic cortex was increased selectively for the stress-susceptible rats. Conclusions The study was initiated to characterize neuronal substrates associated with stress-coping mechanisms. Six areas, all of which represents limbic structures, were found to be sensitive to stress exposure. The effects within these areas associate to the hedonic status of the rats. Hence, these areas might be associated to stress-coping mechanisms underlying the chronic mild stress induced segregation into stress-susceptible and stress-resilient endophenotypes.